CACNA2D3 Enhances the Chemosensitivity of Esophageal Squamous Cell Carcinoma to Cisplatin via Inducing Ca2+-Mediated Apoptosis and Suppressing PI3K/Akt Pathways - Nie, Changjun; Qin, Xiaohui; Li, Xiaoyan; Tian, Baoqing; Zhao, Ying; Jin, Yuan; Li, Yadan; Wang, Qiang; Zeng, Dingyuan; Hong, An; Chen, Xiaojia (Frontiers in Oncology, 2019)
Resistance to platinum-based combination chemotherapy is the main cause of poor prognosis in patients with advanced esophageal squamous cell carcinoma (ESCC). Previously, we showed that CACNA2D3 (voltage-dependent subunit alpha 2 delta 3 of a calcium channel complex) was significantly downregulated and functioned as a tumor suppressor in ESCC, but its role in the chemosensitivity of ESCC to cisplatin remained unknown. Here, we found that the expression of CACNA2D3 was significantly associated with poor platinum response in ESCC patients from the Gene Expression Omnibus database. Overexpression of CACNA2D3 increased sensitivity to cisplatin in ESCC in vitro, whereas knockdown of CACNA2D3 increased cisplatin resistance. CACNA2D3 promoted cisplatin-induced apoptosis by modulating intracellular Ca2+ stores. In vivo experiments further showed that overexpression of CACNA2D3 enhanced cisplatin anti-tumor effects in a xenograft mouse model. CACNA2D3 overexpression also resulted in the attenuation of PI3K and Akt phosphorylation. Treatment with the PI3K/Akt inhibitor LY294002 restored the chemosensitivity of CACAN2D3-knockdown cells to cisplatin. In conclusion, the results of the current study indicate that CACAN2D3 enhances the chemosensitivity of ESCC to cisplatin via inducing Ca2+-mediated apoptosis and suppressing PI3K/Akt pathways. Therefore, regulating the expression of CACNA2D3 is a potential new strategy to increase the efficacy of cisplatin in ESCC patients.